Evaluation of Anticandidial effect of Antifungal drugs against Candida Isolates - Meena, Bharathi (International Journal of Pharmaceutical & Biological Archive, 2015)
Evaluation of Anticandidial effect of Antifungal drugs against Candida Isolates